COVID-19 and Dengue Combination Dilemma: A Case of Probable Dengue False Positivity in a COVID 19 Patient (Journal of Bangladesh College of Physicians and Surgeons, 2020)
A 58-year-old diabetic and hypertensive patient showed symptoms of fever for seven days with cough and irritation in throat for the same duration. He did not complain of any headache, shivering, confusion, breathlessness, tastelessness or smell abnormalities. His first RT-PCR for coronavirus disease 2019 (COVID-19) and IgM for dengue were both positive. His first PCV value and platelet value were normal on seventh and ninth day respectively. False positive serology for dengue may happen in COVID 19 cases.J Bangladesh Coll Phys Surg 2020; 38(0): 133-135